Biphasic Microdroplet–Microdroplet Extraction for Ultra‐Trace Enriching Analysis. Issue 25 (10th August 2022) - Zhang, Xiaonan; Song, Yongchao; Xu, Tailin; Zhang, Xueji
Abstract: Enriching trace targets from trace samples is essential for analytical chemistry. Here, a mini‐pillar platform for biphasic (aqueous and organic) microdroplet–microdroplet extraction for enrichment analysis is demonstrated. Such mini‐pillars with biphasic hydrophobicity can anchor the biphasic microdroplets (organic or aqueous) regardless of rotation and inversion. Methylene blue (MB) and Nile red (NR) are extracted and analyzed by single‐phase extraction, double‐phase extraction, and enrichment analysis. The results display the well linear relationships of all extraction processes with the high extraction efficiency of more than 80% in the single/double phase and up to 500% in the enrichment phase. This work remedies the deficiencies of traditional liquid phase extraction technology, such as extensive sample consumption, low sensitivity, complex equipment, and cumbersome operation. Furthermore, a portable, easy‐manipulation, low‐waste, high‐throughput, and controllable liquid biphasic platform is proposed for high sensitivity, enrichment, and enhanced biphasic extraction analysis. Abstract : Biphasic microdroplet‐microdroplet extraction for enrichment analysis is demonstrated. The results display the well linear relationships of all extraction processes with the extraction efficiency of above 80% in the single//double phase and up to 500% in the enrichment phase, which heightens the detection sensitivity and manifests excellent prospects in host‐guest recognition chemistries and interface reaction